The Efektivitas Model Pembelajaran Kooperatif Two Stay Two Stray (TSTS) Terhadap Meningkatnya Kreativitas Belajar Pada Mata Pelajaran Pendidikan Agama Kristen Siswa Kelas VII SMP Yabesh School - Sinaga, Dea Cantika; Siregar, Nurliani; Munthe, Bangun (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the effectiveness of the Two Stay Two Stray (TSTS) cooperative learning model in enhancing students' creativity in learning Christian Religious Education at SMP Yabes School Medan. Specifically, the research examines the extent to which TSTS improves creativity through group collaboration and mutual problem-solving. The research method employed is a quantitative approach using a quasi-experimental design. The research sample consists of seventh-grade students at SMP Yabes School Medan. The results show that the TSTS cooperative learning model is effective in increasing students' creativity. This is evident from the improvement in the average scores of students before and after the implementation of the TSTS model. Based on data analysis, it was found that group work and mutual problem-solving significantly contribute to encouraging students to think more creatively and engage actively in the learning process. In conclusion, the TSTS learning model can be used as an effective alternative to enhance students' creativity in learning Christian Religious Education. Therefore, it is recommended that teachers implement this learning model continuously, with further development, to maximize students' learning potential.